2012
DOI: 10.2319/091311-589.1
|View full text |Cite
|
Sign up to set email alerts
|

Bracket bond strength and cariostatic potential of an experimental resin adhesive system containing Portland cement

Abstract: Objective: To determine if a new experimental resin-based material containing Portland cement (PC) can help prevent enamel caries while providing adequate shear bond strength (SBS). Materials and Methods: Brackets were bonded to human premolars with experimental resinbased adhesive pastes composed of three weight rations of resin and PC powder (PC 30, 7:3; PC 50,5:5; PC 70, 3:7; n 5 7). Self-etching primer (SEP) adhesive (Transbond Plus) and resinmodified glass ionomer cement (RMGIC) adhesive (Fuji Ortho FC A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The patient's risk is decisive in all that, but the additional factors such as the materials that are applied may contribute even more. The placing of the fixed device itself disturbs the ecosystem in oral cavity leading toward increasing the number of cariogenic bacteria and the development of white spots [51,52].…”
Section: Table 1 Different Parameters For Calculating the Surface Roughnessmentioning
confidence: 99%
“…The patient's risk is decisive in all that, but the additional factors such as the materials that are applied may contribute even more. The placing of the fixed device itself disturbs the ecosystem in oral cavity leading toward increasing the number of cariogenic bacteria and the development of white spots [51,52].…”
Section: Table 1 Different Parameters For Calculating the Surface Roughnessmentioning
confidence: 99%
“…There is substantial interest in nanomechanical properties of dental biomaterials and tooth structure because of their relevance to the oral environment. For example, nanoindentation has been used to measure changes in enamel properties from orthodontic bracket bonding and tooth coating materials (Iijima et al, ; Kawamura et al, ; Kohda et al, ). The present investigation utilized the nanoindenter to acquire novel information about how the properties of dentin near the biomaterial interface are modified over a three‐month period after placement of two bioceramic products, thus providing new insight about the extent of remineralization.…”
Section: Introductionmentioning
confidence: 99%
“…The use of NiTi arches is widely accepted by the orthodontic community and offers biomechanical benefits difficult to match by some other materials on the market; however, a negative aspect of these arches is the roughness which has the ability to retain a greater amount of dental plaque because it favors its adhesion [2]; principally constituted by aerobic bacteria such as Streptococcus sanguinis and Streptococcus mutans, this plaque propitiates the corrosion of metals and alloys through the formation of organic acids during the 2 Journal of Nanomaterials glycolysis of sugars, reducing the pH [3]. Currently, the search for improvement of existing materials in the field of orthodontics has been a subject of study; for example, the organically modified antibacterial silicates (ORMOSIL) such as quaternary ammonium methacryloxy silicate (QAMS) is added to the orthodontic acrylic resins in order to improve antimicrobial activity and toughness [4], resin-based adhesion materials contain Portland-type cement to provide adequate shear bond strength (SBS) and a caries-preventive effect [5], the incorporation of bioactive glass (BAG) into composite resins (BAG-Bonds) showed the capacity for buffering acidic oral conditions through the liberation of calcium in the environment [6], and also the modification of the arches with the application of nanomaterials, for example, nanoparticles (NPs), is an interesting topic due to popularity carried in recent times, and the advantages above the other modification techniques are low cost through the use of simple devices and easy handling. Between the diverse types of nanomaterials used in order to improve the arches' characteristics, the nanoparticles of TiO 2 have benn shown to be cost-effective [7] and they possess a unique photocatalytic property that results in enhanced microbicide activity, principally against bacterial strains of the plaque [8][9][10] besides their apparently low toxicity and excellent biocompatibility [11,12]; regardless, there is still controversy about it being harmless [13,14], since TiO 2 NPs have been related to the induction of cytotoxicity and genotoxicity due to the production of reactive oxygen species (ROS) in different cell types [15][16][17]; in addition, in vivo studies have shown apparently nanoscale and microscale toxicological effects associated with the size of the nanoparticles of TiO 2 [18,19].…”
Section: Introductionmentioning
confidence: 99%